Sexual dimorphism of nasal index, nasal breadth and nasal height among young Kashmiri population - Gulzar, Shameema; Hussain, Ashaq; Kumar, Irshad Ahmad; Itoo, Mohd Saleem; Mir, Nasir Sayeed (International Journal of Research in Medical Sciences, 2022)
Background: Nose contributes as a very important and prominent part of the face; and occupies the most visible position on normafrontalis. There is an anthropometric harmony between different structures of face including nose, lips, eyes, forehead, chin and cheek. Our study was aimed to determine sexual and ethnic differences in external nose measurements of young adult Kashmiri population and to provide baseline data for reconstructive cosmetic surgeons and forensic experts. Methods: This study was conducted among 300 healthy participants (150 males and 150 females) belonging to Kashmiri population. Nasal height, length and breadth were measured using a vernier caliper. Then, the nasal index was determined for each subject. The obtained data was subjected to statistical analysis. Results: In case of males, mean nasal index was 83.31±12.31 mm, mean nasal length was 57.28±4.51 mm, mean nasal breadth was 48.41 mm and mean nasal height was 36.17±20.9 mm, while in case of females mean nasal index was 226.83±46.41 mm, mean nasal length was 50.16±3.54 mm, mean nasal height was 13.97±2.01 mm and mean nasal breadth was 31.02 mm. Conclusions: Nasal type among the Kashmiri male population is predominantly mesorrhine while in females it is hyperplatyrrine or very wide nose.